Pachygaster hymenaea sp. nov. and P. antiqua James, 1971 (Diptera: Stratiomyidae) in Neotropical ambers - Grund, Martin; Hauser, Martin (Zootaxa, 2005)
We describe Pachygaster hymenaea sp. nov. from Dominican amber from a female specimen and compare it with the only other amber pachygastrine, P. antiqua James, 1971 from Mexican amber. The two species differ by the shape of the ocellar tubercle and the width of the frons. Comments about differences between the holotype of P. antiqua and the original description are given.